Exercise training reduces the acute physiological severity of post‐menopausal hot flushes. (30th December 2015) - Bailey, Tom G.; Cable, N. Timothy; Aziz, Nabil; Atkinson, Greg; Cuthbertson, Daniel J.; Low, David A.; Jones, Helen
Abstract : Key points: A post‐menopausal hot flush consists of profuse physiological elevations in cutaneous vasodilatation and sweating that are accompanied by reduced brain blood flow. These responses can be used to objectively quantify hot flush severity. The impact of an exercise training intervention on the physiological responses occurring during a hot flush is currently unknown. In a preference‐controlled trial involving 21 post‐menopausal women, 16 weeks of supervised moderate intensity exercise training was found to improve cardiorespiratory fitness and attenuate cutaneous vasodilatation, sweating and the reductions in cerebral blood flow during a hot flush. It is concluded that the improvements in fitness that are mediated by 16 weeks of exercise training reduce the severity of physiological symptoms that occur during a post‐menopausal hot flush. Abstract: A hot flush is characterised by feelings of intense heat, profuse elevations in cutaneous vasodilatation and sweating, and reduced brain blood flow. Exercise training reduces self‐reported hot flush severity, but underpinning physiological data are lacking. We hypothesised that exercise training attenuates the changes in cutaneous vasodilatation, sweat rate and cerebral blood flow during a hot flush. In a preference trial, 18 symptomatic post‐menopausal women underwent a passive heat stress to induce hot flushes at baseline and follow‐up. Fourteen participants opted for a 16 week moderate intensity supervised exercise intervention, while seven participants opted for control. Sweat rate, cutaneous vasodilatation, blood pressure, heart rate and middle cerebral artery velocity (MCA v ) were measured during the hot flushes. Data were binned into eight equal segments, each representing 12.5% of hot flush duration. Weekly self‐reported frequency and severity of hot flushes were also recorded at baseline and follow‐up. Following training, mean hot flush sweat rate decreased by 0.04 mg cm 2 min −1 at the chest (95% confidence interval 0.02–0.06, P = 0.01) and by 0.03 mg cm 2 min −1 (0.02–0.05, P = 0.03) at the forearm, compared with negligible changes in control. Training also mediated reductions in cutaneous vasodilatation by 9% (6–12%) at the chest and by 7% (4–9%) at forearm ( P ≤ 0.05). Training attenuated hot flush MCA v by 3.4 cm s −1 (0.7–5.1 cm s −1, P = 0.04) compared with negligible changes in control. Exercise training reduced the self‐reported severity of hot flushes by 109 arbitrary units (80–121, P < 0.001). These data indicate that exercise training leads to parallel reductions in hot flush severity and within‐flush changes in cutaneous vasodilatation, sweating and cerebral blood flow. Key points: A post‐menopausal hot flush consists of profuse physiological elevations in cutaneous vasodilatation and sweating that are accompanied by reduced brain blood flow. These responses can be used to objectively quantify hot flush severity. The impact of an exercise training intervention on the physiological responses occurring during a hot flush is currently unknown. In a preference‐controlled trial involving 21 post‐menopausal women, 16 weeks of supervised moderate intensity exercise training was found to improve cardiorespiratory fitness and attenuate cutaneous vasodilatation, sweating and the reductions in cerebral blood flow during a hot flush. It is concluded that the improvements in fitness that are mediated by 16 weeks of exercise training reduce the severity of physiological symptoms that occur during a post‐menopausal hot flush.